2023
DOI: 10.3390/ijms24021447
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Regeneration in Diabetic Retinopathy: Potentials and Challenges Ahead

Abstract: Diabetic retinopathy (DR), the most common microvascular compilation of diabetes, is the leading cause of vision loss and blindness worldwide. Recent studies indicate that retinal neuron impairment occurs before any noticeable vascular changes in DR, and retinal ganglion cell (RGC) degeneration is one of the earliest signs. Axons of RGCs have little capacity to regenerate after injury, clinically leading the visual functional defects to become irreversible. In the past two decades, tremendous progress has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 143 publications
0
5
0
Order By: Relevance
“…Previously, in addition to vasculopathy, recent studies have also shown retinal neuropathic changes in DR [18][19][20]. As DR progresses, retinal ganglion cells (RGCs) undergo functional impairments [21,22], axonal loss [23,24] and eventually death [25,26]. Since RGCs cannot be replicated or regenerated, the damage of retinal neurons might lead to irreversible vision loss.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, in addition to vasculopathy, recent studies have also shown retinal neuropathic changes in DR [18][19][20]. As DR progresses, retinal ganglion cells (RGCs) undergo functional impairments [21,22], axonal loss [23,24] and eventually death [25,26]. Since RGCs cannot be replicated or regenerated, the damage of retinal neurons might lead to irreversible vision loss.…”
Section: Discussionmentioning
confidence: 99%
“…In the early stage of Diabetes with morphologically unaffected suggesting optic nerve degeneration (11).…”
Section: Optic Nervementioning
confidence: 99%
“…Inadequate infrastructure and limited resources can hinder the implementation of community screening programs. This includes a need for more appropriate facilities, a shortage of qualified healthcare professionals, and limited availability of screening equipment [44].…”
Section: Infrastructure and Resourcesmentioning
confidence: 99%
“…Investment in infrastructure and allocation of adequate resources are essential to overcome these challenges. Developed from articles [40][41][42][43][44].…”
Section: Infrastructure and Resourcesmentioning
confidence: 99%